Scientific opinion on flavouring group evaluation 415 (FGE.415): (E)‐3‐benzo[1, 3]dioxol‐5‐yl‐N, N‐diphenyl‐2‐propenamide. (4th July 2022) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Degen, Gisela; Engel, Karl‐Heinz; Fowler, Paul J; Frutos Fernandez, Maria Jose; Fürst, Peter; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; et al.
Abstract: The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of the substance ( E )‐3‐benzo[1, 3]dioxol‐5‐yl‐ N, N ‐diphenyl‐2‐propenamide [FL‐no: 16.135] as a new flavouring substance, in accordance with Regulation (EC) No 1331/2008. The substance has not been reported to occur naturally and it is chemically synthesised. It is intended to be used as a flavouring substance in specific categories of food, but not intended to be used in beverages. The chronic dietary exposure to [FL‐no: 16.135] estimated using the added portions exposure technique (APET), is calculated to be 780 μg/person per day for a 60‐kg adult and 480 μg/person per day for a 15‐kg 3‐year‐old child. [FL‐no: 16.135] did not show genotoxic effects in bacterial mutagenicity and mammalian cell micronucleus assays in vitro . Developmental toxicity was not observed in a study in rats at the dose levels up to 1, 000 mg/kg body weight (bw) per day. The Panel derived a BMDL of 101 mg/kg bw per day from a 90‐day toxicity study. Based on this BMDL, adequate margins of exposure of 7, 800 and 3, 200 could be calculated for adults and children, respectively. The Panel concluded that there is no safety concern for [FL‐no: 16.135], when used as a flavouring substance at the estimated level of dietary exposure calculated using the APET approach, based on the intended uses and use levels as specified in Appendix B. The Panel further concluded that the combined exposure to [FL‐no: 16.135] from its use as a food flavouring substance and from its presence in toothpaste is also not of safety concern.